'I know it's wrong, but . . .': a qualitative investigation of low‐income parents' feelings of guilt about their child‐feeding practices. Issue 3 (19th June 2012) - Pescud, Melanie; Pettigrew, Simone
Abstract In the developed world, child overweight and obesity rates are highest among the disadvantaged. This has resulted in calls for more research with low socio‐economic families to better understand their experiences with disadvantage and how they might lead to poorer weight outcomes. The present study, conducted in Australia, adopted a qualitative approach to investigate the factors affecting low socio‐economic parents' child‐feeding practices. Methods used to collect data were introspections, interviews and focus groups. In total, 37 parents of overweight or obese children aged between 5 and 9 years took part in the 6‐month study. Guilt emerged as an emotion that parents regularly experienced when allowing their children to consume too much food or foods high in fat, salt and/or sugar. Parents attributed their guilt‐inducing child‐feeding practices to both external and internal factors. Time scarcity and cost were factors that were primarily characterized by an external locus of control. The factors characterized by an internal locus of control were fear of their children experiencing hunger, the perceived need to secure their children's affection through the provision of treat foods, perceptions of their ability to balance their children's diets across eating situations and perceived laziness. Recommendations are provided for addressing guilt‐inducing child‐feeding practices.